Qawa’id Learning Problems Madrasa Aliyah in Indonesia - Rozaanah Rozaanah; Slamet Riyadi (Edumaspul: Jurnal Pendidikan, 2023)
Learning of Arabic grammar in Aliyah madrasahs in Indonesia has not yet achieved the objectives stated in the Decree of the Minister of Religious Affairs number 183 of 2019. There are at least 2 main orientations designed to be mastered by students in Madrasah Aliyah, namely religious and communication orientations. This research examines the causes of this gap and tries to offer solutions based on relevant theories. The method used is literature research, because, with this method, problems can be traced based on research conducted and published over the past 5 years. The sources of data in this writing are journals, books, and other sources that are considered relevant to research. The causes of not achieving the objectives of learning Arabic, especially Arabic grammar in Indonesia include student background, motivation, teaching materials, teacher ability, and teacher tendency in teaching Arabic. The learning of Arabic grammar in the madrasa aliyah has not yet achieved the goals formulated. The solutions offered related to these problems include: increasing the allocation of learning time, using ideal and sustainable teaching materials, increasing teacher competence, and reviewing and simplifying the formulation of Arabic learning objectives in madrasahs..